Effect of Seed Coating and Pelleting on Germination, Plant Establishment and Seed Yield in Cumin (Cuminum cyminum L.) - P. H. Nikumbhe; C. S. Shanttaraja (Annals of Arid Zone, 2024)
An investigation to study the effect of seed coating and pelleting on germination, plant establishment, and seed yield of cumin was conducted at ICAR-Central Arid Zone Research Institute, Jodhpur, during the Rabi season in the year 2016 and 2017. The field experiment was laid out in a randomized complete block design, comprising 18 treatments in three replications. Results revealed that, pelleting of seeds with lignite + Azospirillum significantly increased per cent field emergence (91.5%), plant height, umbels per plant, seeds per plant and seed yield as compared to other treatments. But seed yield parameters viz. days required for 50% t field emergence, plant height at harvesting time, days required for 50% flowering and seed test weight did not show significant variation with other treatments. Furthermore, an experiment on the storability of pelleted seeds in terms of germination percentage was conducted in a laboratory, and it was found that seeds pelleted with lignite and Azospirillum recorded the highest germination percentage (67%) at the end of a 6-month storage period. Overall, seed pelleting treatments with lignite + Azospirillum improved crop establishment, growth, and seed yield, and the pelleted seeds can also be stored for 6 months under ambient conditions.